Liberdade religiosa e intolerância em práticas de igrejas neopentecostais na apreciação de casos julgados pelo Poder Judiciário brasileiro - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The presented dissertation has as its object the analysis of freedom and intolerance both in the religious context, worked in historical perspectives and in the presentation of these themes in the present time. We will seek to show how religious freedom, which was born as a historic achievement in the context of democratic states of law or in its formative process, contradictorily makes itself a driving force of religious intolerance and how these are appreciated in the face of legal norms, which aim to balance relations within the democratic rule of law to maintain its hegemony. The problem is fixed in determining whether there is a legal or hermeneutic framework used by the Brazilian legal system, capable of setting the limit between religious freedom and the practice of intolerance. Therefore, the general objective is to analyze whether these limits exist and where they are. As for the methodology, a qualitative approach was proposed, using the deductive method in its development with the use of bibliographical and documental research. The temporal cut begins in the period after the enactment of the Federal Constitution of 1988, when religious freedom was elevated to the category of right and fundamental guarantee, and ends at present. A historical retreat underpins the cultural and religious origins assimilated in the West and consequently in Brazil. With an analysis of the construction of Hebrew and Christian monotheism, and the dogmas established from the ascension of Yahweh as God One. Creating an anachronistic background that intensifies the understanding of concepts and configures research in the context of history, at the same time directs the parameters for the analysis of sources. Among the sources, primary sources consisting of selected cases decided in Brazilian courts will be analyzed.
Keywords: Religião; Liberdade religiosa; Intolerância religiosa; Neopentecostal; Limite da liberdade religiosa; Religion; Religious freedom; Religious intolerance; Neopentecostals; Limit of religious freedom; CIENCIAS HUMANAS::HISTORIA; TEOLOGIA::HISTORIA DA TEOLOGIA; CIENCIAS HUMANAS::TEOLOGIA